2022
DOI: 10.1101/2022.05.31.493627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Highly-Automated, High-Throughput Replication of Yeast-based Logic Circuit Design Assessments

Abstract: We describe an experimental campaign that replicated the performance assessment of logic gates engineered into cells of S. cerevisiae by Gander, et al. Our experimental campaign used a novel high throughput experimentation framework developed under DARPA's Synergistic Discovery and Design (SD2) program: a remote robotic lab at Strateos executed a parameterized experimental protocol. Using this protocol and robotic execution, we generated two orders of magnitude more flow cytometry data than the original experi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The performance of a circuit is evaluated as a circuit’s ability to express fluorescence (ON) or not (OFF) as intended by the circuit’s logic given the presence or absence of chemical inputs. Logic circuits designed to exhibit OR and NOR logic were chosen based on preliminary data analysis in which previously built OR and NOR circuits performed poorly ((4; 39) and Fig. 6 in (25)).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of a circuit is evaluated as a circuit’s ability to express fluorescence (ON) or not (OFF) as intended by the circuit’s logic given the presence or absence of chemical inputs. Logic circuits designed to exhibit OR and NOR logic were chosen based on preliminary data analysis in which previously built OR and NOR circuits performed poorly ((4; 39) and Fig. 6 in (25)).…”
Section: Introductionmentioning
confidence: 99%
“…With further examination, it was observed that the provenance of the OR strains is not clear, and that there may have been an error in the labeling or construction of one or more OR strains. This is backed by inconsistencies between the reported strain sequence, the sequence uploaded to SynBioHub [11], DNAseq [16], and small RNAseq experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Such laboratories enable the full automation of the design-make-test-analyze (DMTA) cycle [35]. Some examples of automated DMTA have shown promise in protein engineering [36], synthetic biology [15], and chemical synthesis [14]. The coupling of automated data generation and AI-driven experimentation may introduce new paradigms of automated experimentation with no reliance on "man-in-the-loop" [36].…”
Section: Introductionmentioning
confidence: 99%